Collaborative Tourism Governance: Design’s Edutourism Program at Geopark Kebumen - Nugroho, Muhammad Farid; Dianingsih, Regina Cahya; Irmawati, Ade; Annshori, Muhammad Faqih (JIAN (Jurnal Ilmiah Administrasi Negara), 2026)
Collaborative governance is increasingly recognized as a more reliable approach to problem-solving compared to efforts conducted solely by government institutions, particularly in the tourism sector. This study aims to examine the collaborative tourism model applied in designing an edutourism program in the Kebumen Geopark and to formulate a governance framework that supports its development. Using a mixed-methods approach, the research analyzes secondary data related to stakeholder activities, events, and coordination meetings, complemented by field observations of market specialization through Geopark Corners established in several schools. The findings reveal that effective collaboration among government, educational institutions, local communities, and other stakeholders enables the integration of diverse perspectives and resources. This process results in a comprehensive and strategic edutourism program that not only promotes environmental conservation but also strengthens educational value and local economic empowerment. The study contributes by proposing an integrated edutourism design supported by a participatory governance framework, demonstrating how collaborative governance can bridge multiple interests and create sustainable tourism development.